Scaling and persistence of ozone concentrations in Klang Valley, Malaysia - Muzirah Musa,; Abdul Aziz Jemain,; Wan Zawiah Wan Zin, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The aim of this paper is to describe the characteristics of ozone concentration based on the value of Hurst coefficient. The Hurst coefficient, denoted as H, is used to explain the long-term degree of persistency in ozone concentration in Malaysia. This paper investigates the scaling properties and persistency of ozone concentrations at six selected air quality monitoring stations in Klang Valley, Malaysia. Daily mean for the hourly data of ozone concentration from 1998-2006 is considered in this study. In describing the statistical properties, several related statistics are identified and the autocorrelation functions of the observed data were plotted. The anomaly method is used to deseasonalise the seasonal variation and the natural non-stationary of the data. Next, the persistency of ozone concentration is determined by using the scaling analysis, namely Dispersional Ratio Method. This method considers two dispersion measures, that is the range and variance. The result shows that there are two different scaling regions, separated by a critical time scale, ncwhich is approximately 90 days. For shorter time scale (n <nc), the ozone concentration persists and the concentration is high on higher time scale (n >nc)where the H values are between 0.5 < H < 1 at all monitoring stations. These findings provide information on scaling behaviour and persistence in ozone concentration in the ambient air of Klang Valley, Malaysia.